Malocclusion in a Rabbit – Case Report (Global Journal of Medical Research, 2023)
Dental malocclusion is a highly prevalent pathology in domestic rabbits usually resulting from food management errors The present study aims to report the procedures used in a rabbit treated at the Veterinary Hospital in Jo o Pessoa Para ba affected by this pathology and to highlight the clinical characteristics and the treatment of occlusal adjustment made through tooth wear presented by this species in this condition
Keywords: rabbit; malocclusion; occlusal adjustment; tooth wear